In Vitro Antimalarial, Antimicrobial and Trypanocidal Potentials of the Leaf Extract and Fractions of Bridelia ferruginea (Benth.) - Michael Afolayan; Olayinka Asekun; Oluwole Familoni (Shiraz University of Medical Sciences, 2023)
Bridelia ferruginea Benth. (Euphorbiaceae) is a plant used for various medicinal purposes including the treatment of protozoan infections in many African countries. The present study was aimed to evaluate the in vitro antimalarial, antimicrobial and antitrypanasomal activity of the methanol crude extract and fractions of the medicinal plant, Bridelia ferruginea. Crude extract from dried leaves of Bridelia ferruginea was prepared by cold maceration and fractionated using a reverse phase column under reduced pressure with water - methanol mixtures. The extracts and fractions were tested to determine their biological activities. In vitro antimalarial activity was determined by the plasmodial lactate dehydrogenase culture sensitivity assay while antitrypanosomal activity was tested in vitro against a culture of Trypanosoma brucei promastigotes. The crude extract of B. ferruginea exhibited significant antitrypanasomal activity with an IC50 of 8.48 µg/mL which was further enhanced in some of the fractions like the MeOH fraction (BFD) with an IC50 of 1.04 µg/Ml which indicates very good activity. Sub - fraction BFF (obtained from 1:3 H2O:MeOH fraction - BFC) exhibited the best antimalarial activity among all the fractions and sub - fractions with an IC50 value of 19.73 µg/mL against P. falciparum D6 and 20.49 µg/mL against P. falciparum W2. There was no observable antibacterial or antifungal activity for all crude extracts, fractions and sub - fractions. The results from this study have validated the leaves of Bridelia ferruginea as potential sources of antimalarial and antitrypanosomal agents which can serve as a lead in drug development.